Impact of physical therapy on various variants of Parkinson’s disease - Labinsky, Andriy (Journal of Education, Health and Sport, 2017)
Topicality. To determine the effectiveness of the use of physical therapy in Parkinson’s disease with different onset (early and late) course of the disease and the level of blood pressure. Objectives of the study: to develop and apply to patientswith various forms with Parkinson’s disease with predominantly non-motor manifestations program of physical therapy. To study the effectiveness of the developed physical therapy program on the scale of assessment of the state of non-motor symptoms, mental disorders and cognitive impairment in early and late onset of Parkinson’s disease with different levels of blood pressure. Research results. After the physical therapy, the condition of the patients improved in all groups of patients surveyed not to the same extent. Improvement was more commonly observed in groups of patients with early onset Parkinson’s disease with relatively normal blood pressure, with the use of exercise and the entire range of physical therapy we developed. Changes in the status of patients after physical therapy for the better were recorded by both subjective and objective survey data. Particularly significant were the data from the study on the scale of assessment of patients with non-motor manifestations of Parkinson’s disease (scale of non-motor symptoms – NMSS, scale of mental disorders – MMSE, Montreal scale of cognitive disorders-MOCA). They demonstrated a significant statistically difference between control and study groups of patients with normal blood pressure toward improvement in the final examination scores. Conclusions. The condition of patients with normal blood pressure and early onset of the disease who received the developed complex of physical therapy according to the studies was significantly better than in the group of patients who did not receive physical therapy with high blood pressure, which testifies to the higher efficiency of the developed by us and applied complex physical therapy of non-motor manifestations of Parkinson’s disease in patients with early-onset development of Parkinson’s disease with normal blood pressure.